The legal nature of international human rights - Addo, Michael K. (International studies in human rights ;, 2010)
The role and influence human rights in society has been enhanced by its association with international law and yet despite this legal springboard, the scope of its legal nature remains uncertain. By analysing the work of international human rights courts and treaty bodies alongside a brief historical review, this book assesses the distinctive legal dimension of human rights. It concludes that the legalisation of human rights is an unplanned and evolving social construct that continues under the managerial oversight of international human rights courts and treaty bodies which employ the primary.